The Impact of Violence on the Anxiety Levels of Healthcare Personnel During the COVID-19 Pandemic - Bitencourt, Mariá Romanio; Silva, Lincoln Luís; Alarcão, Ana Carolina Jacinto; Dutra, Amanda de Carvalho; Bitencourt, Marcos Rogério; Garcia, Giovana Jorge; de Andrade, Luciano; Nickenig Vissoci, João Ricardo; Pelloso, Sandra Marisa; Carvalho, Maria Dalva de Barros (Frontiers in Psychiatry, 2021)
Introduction: The COVID-19 pandemic stressed the importance of healthcare personnel. However, there is evidence of an increase in violence against them, which brings consequences, such as anxiety. The aim of this study was to analyze the anxiety levels of health professionals who have or not suffered violence during the COVID-19 pandemic, and verify the variables associated with the risk of starting to take medication for anxiety. Methods: We assessed the anxiety profile of health professionals in Brazil through an online questionnaire, using the Generalized Anxiety Disorder 7-item Scale (GAD-7), in relation to groups of participants who have or not suffered violence during the COVID-19 pandemic. We used Cronbach's alpha reliability coefficient to check the consistency of the responses, and the effect size using the r coefficient. Principal Component Analysis was used to verify the differences in anxiety scores between the two groups. Logistic regression analysis was also used to verify the variables associated with the risk of starting medication for anxiety and considered statistically significant when p <0.05. Results: A total of 1,166 health professionals participated in the study, in which 34.13% had a normal anxiety profile, 40.14% mild, 15.78% moderate, and 9.95% severe. The mean score of the sum of the GAD-7 was 7.03 (SD 5.20). The group that suffered violence had a higher mean (8.40; SD5.42) compared to the group that did not (5.70; SD4.60). In addition, the median between both groups was significantly different (7.0 vs 5.0; p <0.01). Approximately 18.70% of the participants reported having started taking medication to treat anxiety during the pandemic. The factors that increased the chances of these professionals starting medication for anxiety (p <0.05) were having suffered violence during the pandemic (OR 1.97; 95% CI 1.42–2.77), being nurses (OR 1.61; 95% CI 1.04–2.47) or other types of health professionals (OR 1.58; 95% CI 1.04–2.38), and having a mild (OR 2.11; 95% CI 1.37–3.34), moderate (OR 4.05; 95% CI 2.48–6.71) or severe (OR 9.08; 95% CI 5.39–15.6) anxiety level. Conclusion: Brazilian healthcare professionals who have suffered violence during the pandemic have higher anxiety scores and higher risk to start taking anxiety medication.